Criminal Prosecution in the Criminal Procedure of the Republic of Armenia - Dilbandyan, Samvel (Bulletin of Yerevan University C: Jurisprudence, 2023)
This article is dedicated to the issues of criminal prosecution in criminal procedure. In the current Code of Criminal Procedure, a new ideology was introduced for the implementation of criminal procedure problems in pre-trial proceedings. In the criminal proceedings, the criminal prosecution has a significant role, it determines the further course of the criminal proceedings and the boundaries of the investigation. Criminal prosecution is apparently the driving force behind criminal proceedings, which means that the further course of criminal proceedings is determined by it. Undoubtedly, it is also important for ensuring the protection of human rights within the framework of criminal proceedings. So far, the issues of initiation and implementation of criminal prosecution have remained unresolved in the theory and practice of criminal procedure. Although the criminal procedure legislation regulates in detail the legal bases of criminal prosecution, some important issues remain unsettled. Today, the replacement of the terms of the criminal proceedings with the terms of the criminal prosecution has caused problems in the implementation of the right to defend for the persons who were actually prosecuted, in particular, the said person is deprived of the opportunity to exercise the fundamental rights of the accused. The essence of the problem lies in the fact that the body conducting the proceedings, in order to fit within the terms of criminal prosecution set by the law, strives to give a later status to the person actually prosecuted, in order to fit within the stated terms. Meanwhile, the body conducting the proceedings performs such procedural actions throughout the criminal proceedings that affect the legitimate interests of the person who is actually under criminal prosecution.